Methodology for the selection of compensation trade tools in SMEs - František Milichovský (DANUBE: Law, Economics and Social Issues Review, 2014)
The main aim of this paper is to determine which factors of business tools are important in Czech companies. To find these factors, theoretical information from the area of trade tools and data from primary research (obtained via questionnaire) were used. These data are applied by a statistical evaluation of selected indicators which could help determine the significance of the indicators in the area being monitored. Activities concerning the management of company finances are also partially incorporated, as due to their close cohesion with business, they cannot be excluded from the field of turnaround management. The business tools described in the paper see excellent usage not only during times of crisis but also in periods of prosperity, when their application provides companies with unique competitive advantages as a way of increasing GDP. The results of the paper confirm the necessity for compensation tools in the business environment and provide the significance level of the compensation tools used. Accurate usage could create an advantage in a global market characterised by high competition.
Keywords: 330; Compensation Trades; Trading Tools; Crisis Management; SMEs